Indikator Keselamatan Kerja Pada Aktivitas Bongkar Muat di Pelabuhan - Apzur Rohimah Putri; Susilawati S (Yayasan Daarul Huda Kruengmane, 2023)
The port is one of the inter-island and international trade chains. In loading and unloading activities, the thing that must be prioritized is occupational safety and health. Occupational safety is an effort to guarantee the integrity and safety of workers and the environment. Occupational safety is one of the factors that absolutely must be fulfilled so that workers can work safely and optimally in accordance with the duties of the workforce, with a careful attitude and not being careless in acting will make other parties not experience worry. The research method used is the analysis of journal articles in the form of library research which takes several previous studies which make a new study. Aims to increase knowledge and insight about K3. In loading and unloading at the Port, the following must be considered: the safety and health of workers which includes the use of safety equipment, the use of PPE, the attitude of workers and risk control. The results of analysis from several journals regarding work safety indicators in loading and unloading activities at the Port, the use of safety equipment for stevedoring employees in order to support the process of loading and unloading at the port is less than optimal, this can cause risks, and the safety and health of unloading workers is not guaranteed. load at this port, thus hindering the ongoing work.